Preparedness for future pandemics: Utilizing psychological first aid in disaster mental health-care training - Miriam Archana Simon; Amal Saleh Al-Ghailani (Wolters Kluwer Medknow Publications, 2024)
The COVID-19 pandemic has had an immense global impact on health-care delivery and health-care training. One of the vital lessons learned in the postpandemic phase is to address the requirements for growing mental health-care concerns worldwide. In view of preparedness for similar disasters in the future, it is essential to create viable pathways that proactively tackle mental health crises. Measures to improve community resilience, through training in psychological first aid (PFA), as an intervention for disaster recovery and disaster management may prove beneficial. This may be achieved by training professionals and residents in the local community. In addition, training in PFA may be focused on first responders and frontline workers. Furthermore, training in disaster mental healthcare may be introduced as a curricular initiative for students in the health-care profession. This will be directly reflected in society's preparedness for disasters and emergencies in the future. An initiative for training in PFA as part of the undergraduate curriculum has been introduced for medical students in Oman. In addition to contributing to personal wellbeing, it is anticipated that the training module will equip students to effectively contribute to the management of disasters and emergencies.